KOMPUTER JAKO NARZĘDZIE PRZESTĘPSTWA - Szczepaniec, Maria (Zeszyty Prawnicze, 2016)
The Computer as the Tool of the Crime Summary The article presented the classification of computer crimes on the basis of Polish criminal law and some issues concerning computer crime. Was also presented a brief analysis of selected computer crime, such as: grooming and computer cheating. The article describes also questions concerning security of cyberspace.